The Determinants of Efficiency in Turkish Banking Sector After Global Finacial Crisis - Ferda Keskin Onen; İbrahim Tunik (European Scientific Journal, ESJ, 2017)
In this study, we analyzed the efficiency changes of the Turkish banking sector between the years 2005-2014, when the global financial crisis was experienced. Data Envelopment Analysis (DEA) methodology was applied to obtain efficiency scores. Then, panel regression analysis was performed to explore the main determinants of efficiency changes. The findings have shown that internal factors are more effective than external ones on banks efficiency. The financial crisis was found to have a slight impact on banks’ efficiency in managing their financial resources. GDP and inflation had negative relationship with bank efficiency due to the unanticipated inflation rate and volatile economic growth. The empirical findings imply that more efficient banks generate higher returns accordingly.